2021
DOI: 10.3389/fimmu.2021.603416
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the Pyroptosis-Related Inflammasome Pathway in the Pathogenesis of Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is a major cause of chronic kidney disease (CKD) in many developed and developing countries. Pyroptosis is a recently discovered form of programmed cell death (PCD). With progress in research on DKD, researchers have become increasingly interested in elucidating the role of pyroptosis in DKD pathogenesis. This review focuses on the three pathways of pyroptosis generation: the canonical inflammasome, non-canonical inflammasome, and caspase-3-mediated inflammasome pathways. The mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 122 publications
0
38
0
Order By: Relevance
“…However, it is reported that gasdermin E (GSDME) cleavage by caspase-3 liberates the GSDME-N domain and mediates pyroptosis by forming pores in the plasma membrane. Caspase-3-mediated inflammasome pathway is also a pathway of pyroptosis generation in DKD (Liu et al, 2021). The effect of TFA in regulating apoptosis and caspase-3-mediated inflammasome pathway will be focused in our further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is reported that gasdermin E (GSDME) cleavage by caspase-3 liberates the GSDME-N domain and mediates pyroptosis by forming pores in the plasma membrane. Caspase-3-mediated inflammasome pathway is also a pathway of pyroptosis generation in DKD (Liu et al, 2021). The effect of TFA in regulating apoptosis and caspase-3-mediated inflammasome pathway will be focused in our further study.…”
Section: Discussionmentioning
confidence: 99%
“…It is initiated by oxidative perturbations in the intracellular microenvironment, which are constitutively controlled by glutathione peroxidase 4 (GPX4) and can be inhibited by iron-chelating agents and lipophilic antioxidants [ 9 ]. Ferroptosis is distinguished from apoptosis [ 10 ], necrosis [ 11 ], autophagy [ 12 ], and pyroptosis [ 13 ] by a varying set of morphological characteristics, inducing factors, and regulatory pathways.…”
Section: Morphological Characteristics Of Ferroptosismentioning
confidence: 99%
“…In addition to inflammatory cascades, the activated NLRP3 inflammasome also promoted GSDMD-executed pyroptosis, a kind of programmed cell death [7,14,15]. Several lines of studies indicated that pyroptosis was involved in the pathogenesis of diabetes and its complications, such as diabetic nephropathy [49,50], diabetic retinopathy [51][52][53], and diabetic cardiomyopathy [18,54,55]. However, whether GSDMD-executed pyroptosis was involved in the pathogenesis of DK remained unknown.…”
Section: Discussionmentioning
confidence: 99%